Judicial Ijtihād and Maqāṣid-Based Adjudication in Interfaith Inheritance: Reconstructing Wasiat Wajibah in Indonesian Islamic Law - Siti Ropiah; Syafi’i Syafi’i; Abdul Rahim; Hisam Ahyani; Miftakhul Huda; Salisu Muhammad Gumel (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2026)
Abstract: Islamic inheritance law in Indonesia encounters persistent normative tension when applied to interfaith family structures. Classical farāʾiḍ doctrine categorically prohibits inheritance across religious boundaries, a rule that frequently generates substantive injustice within plural legal and social contexts. In response, Indonesian Supreme Court jurisprudence has progressively developed wasiat wajibah (mandatory will) as a judicial mechanism for protecting non-Muslim family members who are excluded from intestate succession. Therefore, this study aimed to examine the jurisprudential development, legal construction, and normative limits of wasiat wajibah through doctrinal analysis of authoritative Supreme Court decisions issued between 1995 and 2018, supported by statutory interpretation and relevant Islamic legal scholarship. A normative-juridical approach was adopted, incorporating doctrinal, jurisprudential, and comparative legal analysis, while a limited empirical interview with a Religious Court judge was included solely to provide contextual illustration rather than as representative evidence of national judicial practice. The results showed that Indonesian courts have gradually transformed wasiat wajibah from a discretionary equitable remedy into an institutionalised judicial doctrine applied through purposive interpretation, subject to a one-third quantitative limitation and procedural safeguards. The analysis further indicated that this jurisprudential development reflects a form of judicial ijtihād qadhaʾī grounded in maqāṣid al-sharīʿah, particularly the protection of wealth, family integrity, and human dignity. At the same time, an unresolved normative issue was identified concerning the judicial extension of Article 209 of the Compilation of Islamic Law to non-Muslim beneficiaries, indicating continuing debates over the scope of judicial law-making (rechtsvorming) within Indonesian Islamic inheritance law. Indonesian courts use wasiat wajibah, a supplementary legal mechanism designed to reconcile classical inheritance doctrine with substantive justice in a plural legal system, instead of redefining non-Muslims as legal heirs.